Respuesta :

irspow
x+4y=3  subtract 4y from both sides

x=3-4y

2x-3y=17, using x found above becomes:

2(3-4y)-3y=17 perform indicated multiplication on left side

6-8y-3y=17  combine like terms on left side

6-11y=17  subtract 6 from both sides

-11y=11  divide both sides by -11

y=-1, using this y in x+4y=3 becomes:

x+4(-1)=3

x-4=3  add 4 to both sides

x=7

So the solution to the system of equation is the point (7, -1)
cher
Equation 1)  x + 4y = 3
Equation 2)  2x - 3y = 17

Multiply ALL of equation 1 by 2 so that both equations have (2x) in it.

1)  2(x + 4y = 3)

Simplify.

1)  2x + 8y = 6
2)  2x - 3y = 17

Subtract equations from one another.

11y = -11

Divide both sides by 11.

y = -1

Plug in -1 for y in the first equation.

x + 4y = 3

x + 4(-1) = 3

Simplify.

x - 4 = 3

Add 4 to both sides.

x = 7

x = 7, y = -1

~Hope I helped!~